2015
DOI: 10.1002/pssc.201510211
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase silanization for silicon nanowire sensors and other lab‐on‐a‐chip systems

Abstract: Designing a microfabrication process for lab-on-a-chip systems can at times be challenging, and the need to integrate a chemical surface modification reaction into this process can limit the options. Therefore, a robust set-up and protocol for the gas phase modification has been developed that can be variably integrated into microfabrication processes. The main improvement compared to similar methods is, besides easy and versatile sample handling, the integration of a continuous argon flow percolating through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In addition to improving the adhesion, the SAMs also help in achieving highly smooth gold films [21]. Earlier reports on vapour-and liquid-phase deposition of MPTMS monolayer involved a process time that was a few hours to 1 week long [18][19][20][21][22][23][24][25][26]. For practical applications, one needs to have faster deposition methods that help the adhesion of gold to substrates as well as smooth, uniformly covered few monolayer gold films.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to improving the adhesion, the SAMs also help in achieving highly smooth gold films [21]. Earlier reports on vapour-and liquid-phase deposition of MPTMS monolayer involved a process time that was a few hours to 1 week long [18][19][20][21][22][23][24][25][26]. For practical applications, one needs to have faster deposition methods that help the adhesion of gold to substrates as well as smooth, uniformly covered few monolayer gold films.…”
Section: Introductionmentioning
confidence: 99%
“…Then, 100 nm thick Au electrical contacts with 5 nm Ti as adhesive layer were placed by thermal evaporation using electron beam (e-beam) lithography in a lift-off process with polymethyl methacrylate e-beam resist. Previous experiments have shown that thus integrated nanowires with an equivalent level of doping typically show ohmic contact behavior [16].…”
Section: Kinked P-n Junctions For Measurements Of Single Sinwsmentioning
confidence: 99%
“…Molecules can be directly adsorbed on the SiNW surface through hydrogen bonding, van der Waals forces, or hydrophobic interactions, but this might not be the optimal strategy, since the long-term stability will be compromised. Silanization is a classical silicon surface modification technique extensively used on silicon nanowires, [65,[151][152][153][154] where silicon atom containing molecules covalently bind leaving a variety of functional groups, depending on the specific chosen silane molecule. Chemical modifications of the silicon surface are usually done to create strong bonds between the bioreceptor and the nanowire.…”
Section: Sensing Biomolecules: Toward Miniaturized Point-of-care Diagmentioning
confidence: 99%
“…The chemistry of silicon is well known and, unlike other materials also implemented in FETs like carbon nanotubes, graphene, or MoS 2 , it allows easy implementation of covalent bonds on its hydroxyl‐rich surface. Silanization is a classical silicon surface modification technique extensively used on silicon nanowires, where silicon atom containing molecules covalently bind leaving a variety of functional groups, depending on the specific chosen silane molecule. Some examples include APTES with amino groups, 3‐(triethoxysilyl)propylsuccinic anhydride (TESPSA) with succinic anhydride functionality, or octadecyldimethylmethoxysilane (ODMS) with no reactive groups for passivation (Figure b).…”
Section: Biochemically Configurable Hybrid Devices (Biosensors)mentioning
confidence: 99%